Towards the controlled enzymatic synthesis of LNA containing oligonucleotides - Sabat, Nazarii; Katkevica, Dace; Pajuste, Karlis; Flamme, Marie; Stämpfli, Andreas; Katkevics, Martins; Hanlon, Steven; Bisagni, Serena; Püntener, Kurt; Sladojevich, Filippo; Hollenstein, Marcel (Frontiers in Chemistry, 2023)
Enzymatic, de novo XNA synthesis represents an alternative method for the production of long oligonucleotides containing chemical modifications at distinct locations. While such an approach is currently developed for DNA, controlled enzymatic synthesis of XNA remains at a relative state of infancy. In order to protect the masking groups of 3′-O-modified LNA and DNA nucleotides against removal caused by phosphatase and esterase activities of polymerases, we report the synthesis and biochemical characterization of nucleotides equipped with ether and robust ester moieties. While the resulting ester-modified nucleotides appear to be poor substrates for polymerases, ether-blocked LNA and DNA nucleotides are readily incorporated into DNA. However, removal of the protecting groups and modest incorporation yields represent obstacles for LNA synthesis via this route. On the other hand, we have also shown that the template-independent RNA polymerase PUP represents a valid alternative to the TdT and we have also explored the possibility of using engineered DNA polymerases to increase substrate tolerance for such heavily modified nucleotide analogs.